Commited to Flexible Fiscal Rules - Laura Pagenhardt; Christoph Große Steffen; Malte Rieth (ZBW - Leibniz Information Centre for Economics, 2021)
We study the impact of fiscal rules on macroeconomic performance following natural disaster shocks, using dynamic panel models and quarterly data for 89 countries. We find that countries with fiscal rules perform significantly better in the aftermath of such shocks than countries without rules. GDP, private consumption and investment are persistently higher. The superior performance is associated with more expansionary fiscal policy, which hinges critically on larger fiscal space and escape clauses. We rationalize the findings in a quantitative model of sovereign default. The model replicates the empirical dynamics and shows that tight fiscal rules create fiscal space in good times that can be used in bad times for deficit-spending.
Keywords: E62; C32; E32; H50; 330; Fiscal policy; fiscal regimes; natural disasters